Determining negativity in selected 2015 presidential election campaigns press advertisements (2020)
This paper reviews the message content of selected adverts used during the 2015 Presidential election campaigns with a view to identifying the extent to which negative content was employed. Traditionally, political parties hold rallies and engage in public Speeches across major geo- political zones prior to elections. Campaign messages are now disseminated via the broadcast and print media along with online engagements from Twitter to Facebook. Using the Functional theory of Campaign discourse as the background, the study examined 20 purposively selected print ads from 4 (four) major Nigerian Newspapers. Using content and descriptive analysis, the researcher looked at the headline, body copy, Illustration, call to action and Sponsor of the selected advert Findings show that many of the print ads were direct criticisms and verbal attacks on the character and judgment of the contestants. Messages bothered on direct name calling and attack on personality and character of one’s opponents. Many of the adverts did not have identified Sponsors and in some instances Sponsors simply called themselves Concerned Citizens or similar appellations. Many of the messages by- passed APCON's gate-keeping and received cooperation from media houses who ran adverts that were not vetted by APCON. The paper recommends stricter penalties against offensive and inciting political advertisements